Abject Performances : Aesthetic Strategies in Latino Cultural Production - Alvarado, Leticia, 1982- (Book collections on Project MUSE., 2018)
In Abject Performances Leticia Alvarado draws out the irreverent, disruptive aesthetic strategies used by Latino artists and cultural producers who shun standards of respectability that are typically used to conjure concrete minority identities. In place of works imbued with pride, redemption, or celebration, artists such as Ana Mendieta, Nao Bustamante, and the Chicano art collective known as Asco employ negative affects--shame, disgust, and unbelonging--to capture experiences that lie at the edge of the mainstream, inspirational Latino-centered social justice struggles. Drawing from a diverse expressive archive that ranges from performance art to performative testimonies of personal faith-based subjection, Alvarado illuminates modes of community formation and social critique defined by a refusal of identitarian coherence that nonetheless coalesce into Latino affiliation and possibility.